Glutaric aciduria type 1 in children. Clinical presentation of 46 cases in Russian families - S. V. Mikhailova (Nervno-Myšečnye Bolezni, 2021)
Background. Glutaric aciduria type 1 is an autosomal recessive disease caused by mutations in the GCDH gene, which encodes the enzyme glutaryl‑CoA dehydrogenase. Metabolic crisis in type 1 glutaric aciduria is an acute life‑threatening condition that requires careful diagnosis with a number of other conditions and the immediate initiation of pathogenetic therapy.Materials and methods. Clinical manifestations, neuroimaging characteristics of the disease were studied in 46 patients with diagnosed glutaric aciduria type 1 confirmed by biochemical and molecular genetic methods. Methods: gas chromatography with mass spectrometry, tandem mass spectrometry, Sanger sequencing, chromosomal microarray analysis of the exon level.Results and discussion. A retrospective analysis of anamnestic and clinical data was carried out, and the nature and age of disease manifestation, provoking factors, a spectrum of clinical manifestations and neuroimaging data were assessed.Conclusion. How initiated treatment prevents progression of neurological symptom relief and patient adaptation. With the help of the goal, it is necessary to inform pediatricians, neurologists and neuroradiologists about this feature of the course of glutaric aciduria type 1 in order to increase the clinical alertness of this disease.